Diphenyl diselenide dietary supplementation alleviates behavior impairment and brain damage in grass carp (Ctenopharyngodon idella) exposed to methylmercury chloride - Baldissera M.D. (2020)
© 2019 Elsevier Inc.Mercury (Hg) induces neurobehavioral disorders through reactive oxygen species (ROS) elevation and impairment of brain key enzyme activities. Nevertheless, the therapeutic and toxic selenium concentrations for fish are very close; diphenyl diselenide (Ph2Se2), an organoselenium compound with neuroprotective effects, may be an alternative to elemental Se. Therefore, the aim of this study was to determine whether dietary supplementation with Ph2Se2 prevented or reduced the neurobehavioral alterations and oxidative damage elicited by CH3HgCl in grass carp Ctenopharyngodon idella. Fish exposed to CH3HgCl exhibited significantly reduced distance travelled and swimming speed compared to the control group, as well as augmented cortisol and ROS levels and xanthine oxidase (XO) activities. CH3HgCl exposure significantly increased lipid peroxidation (LOOH) and protein carbonylation (PC) levels compared to those of the control group, while acetylcholinesterase (AChE) and sodium-potassium pump (Na+, K+-ATPase) activities were inhibited. Dietary supplementation with 3 mg/kg Ph2Se2 ameliorated locomotor activity impairment and prevented the augmented brain cortisol and ROS levels as well as XO activity. The supplement reduced lipid and protein damage elicited by CH3HgCl and exerted protective effects on brain AChE and Na+, K+-ATPase activities. Exposure to an environmental concentration of CH3HgCl elicited neurobehavioral alterations linked to reduced locomotor activity, a finding that can be explained by oxidative damage and reduced activity of AChE and Na+, K+-ATPase in telencephalon and mesencephalon structures. Dietary supplementation with Ph2Se2 prevented CH3HgCl-induced locomotor impairment. This effect appeared to be mediated by antioxidant action. Ph2Se2 may be a viable approach to prevention or reduction CH3HgCl-mediated neurotoxic effects.